Comparison of a ready-to-use liquid glucagon injection administered by autoinjector to glucagon emergency kit for the symptomatic relief of severe hypoglycemia: two randomized crossover non-inferiority studies - Anh Nguyen; Mark P Christiansen; Martin Cummins; Steven Prestrelski; Nicole C Close; Khaled Junaidi (BMJ Open Diabetes Research & Care)
Introduction To prevent medical sequelae of severe hypoglycemic emergencies, prompt and reliable rescue intervention is critically important. A ready-to-use, liquid stable glucagon, administered subcutaneously by glucagon autoinjector (GAI), Gvoke HypoPen (glucagon injection; Xeris Pharmaceuticals), was evaluated for rescue treatment of severe hypoglycemia.Research design and methods Two phase III, randomized, controlled, blinded, non-inferiority crossover studies were conducted in 161 adults with type 1 diabetes to compare 1 mg doses of GAI versus glucagon emergency kit (GEK) for treating insulin-induced severe hypoglycemia. Efficacy was evaluated as either a return of plasma glucose to >70 mg/dL (3.9 mmol/L) or increase ≥20 mg/dL (1.1 mmol/L) from a baseline glucose of <50 mg/dL (2.9 mmol/L), within 30 min of dosing.Results For successful plasma glucose recovery within 30 min, treatment with GAI was non-inferior to GEK. Treatment with GAI was non-inferior to GEK for a plasma glucose >70 mg/dL (3.9 mmol/L) or neuroglycopenic symptom relief within 30 min. From administration of glucagon, the mean time to achieve plasma glucose >70 mg/dL (3.9 mmol/L) or increase ≥20 mg/dL (1.1 mmol/L) was 13.8±5.6 min for GAI and 10.0±3.6 min for GEK. This mean time does not account for the significantly shorter (p<0.0001) drug preparation and administration time for GAI (27.3±19.7 s) versus GEK (97.2±45.1 s). The incidence of treatment emergent adverse events was comparable in both groups.Conclusions A ready-to-use GAI was non-inferior to GEK, with a similar tolerability profile. GAI is an effective, safe, and well-tolerated rescue treatment for severe hypoglycemia and is a viable alternative to GEK.Trial registration numbers NCT02656069 and NCT03439072.